Boson peak, heterogeneity and intermediate-range order in binary SiO2-Al2O3 glasses - Ando, Mariana F.; Benzine, Omar; Pan, Zhiwen; Garden, Jean-Luc; Wondraczek, Katrin; Grimm, Stephan; Schuster, Kay; Wondraczek, Lothar (Scientific Reports, 2018)
In binary aluminosilicate liquids and glasses, heterogeneity on intermediate length scale is a crucial factor for optical fiber performance, determining the lower limit of optical attenuation and Rayleigh scattering, but also clustering and precipitation of optically active dopants, for example, in the fabrication of high-power laser gain media. Here, we consider the low-frequency vibrational modes of such materials for assessing structural heterogeneity on molecular scale. We determine the vibrational density of states VDoS g(ω) using low-temperature heat capacity data. From correlation with low-frequency Raman spectroscopy, we obtain the Raman coupling coefficient. Both experiments allow for the extraction of the average dynamic correlation length as a function of alumina content. We find that this value decreases from about 3.9 nm to 3.3 nm when mildly increasing the alumina content from zero (vitreous silica) to 7 mol%. At the same time, the average inter-particle distance increases slightly due to the presence of oxygen tricluster species. In accordance with Loewensteinian dynamics, this proves that mild alumina doping increases structural homogeneity on molecular scale.
CRIS-Team Scopus Importer:2023-04-20